Guiding intramuscular diaphragm injections using real‐time ultrasound and electromyography. Issue 2 (February 2015) - Sarwal, Aarti; Cartwright, Michael S.; Mitchell, Erin; Williams, Koudy; Walker, Francis O.; Childers, Martin K.
ABSTRACT Introduction: We describe a unique method that combines ultrasound and electromyography to guide intramuscular diaphragm injections in anesthetized large animals. Methods: Ultrasound was used to visualize the diaphragm on each side of spontaneously breathing, anesthetized beagle dogs and cynomolgus macaques. An electromyography (EMG) needle was introduced and directed by ultrasound to confirm that the needle entered the muscular portion of the diaphragm, and methylene blue was injected. Injection accuracy was confirmed upon necropsy by tracking the spread of methylene blue. Results: All methylene blue injections were confirmed to have been placed appropriately into the diaphragm. Conclusions: This study demonstrates the feasibility and accuracy of using ultrasound and EMG to guide injections and to reduce complications associated with conventional blind techniques. Ultrasound guidance can be used for clinical EMG of the diaphragm. Future applications may include targeted diaphragm injections with gene replacement therapy in neuromuscular diseases. Muscle Nerve51: 287–289, 2015